X-ray microtomography observations of xylem embolism in stems of Laurus nobilis are consistent with hydraulic measurements of percentage loss of conductance - Nardini, Andrea (The New phytologist, 2017)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.